An Evaluation of The Status of Qualitative Research in Childhood Education - Rachael Ojima Agarry; Eyiyemi Victoria Ogundele (Indonesian Journal of Multidiciplinary Research, 2023)
The need to evaluate the status of qualitative research, particularly in childhood education, is required. Four questions were answered and three hypotheses were tested. A mixed-method approach design was adopted in this research. The population of the study comprised all childhood education researchers from all the teacher training institutions in Kwara State, Nigeria. 58 researchers were purposively selected to participate in the study. A questionnaire and interview were used to collect the necessary data for the study. The outcome of the study revealed that the qualitative research method is rarely adopted for research related to childhood education. Also, time, secrecy, participants’ unwillingness, cost implication among others were identified as dilemmas to conducting qualitative research in childhood education in the State. The quality of qualitative research conducted in childhood education is on average. The ratio of quantitative research as against qualitative research conducted by childhood educators was found to be 1:8. In other words, there was a significant difference in the number of quantitative and qualitative research conducted. In addition, gender and academic qualification had no significant influence on childhood educators’ use of qualitative research methods. Thus, it was concluded that the status of qualitative research in childhood education in Kwara State, Nigeria is ranked low. Among the recommendations made are training and re-training of teacher trainers of childhood education on the benefits and how to use qualitative research methods.